Peran Orang Tua dalam Pendidikan Karakter Anak Usia Dini - Fitri, Anni Saumi; Widiana, Wika; Atikah, Cucu (Zuriah : Jurnal Pendidikan Anak Usia Dini, 2023)
This research aims to describe the role of parents in early childhood character education. In this research, the method used is literature study. In this method, the data collection system is carried out by collecting data based on the results of research that has been carried out previously which is analyzed and then concluded from the results of the research in order to answer existing problems. Based on the results of a literature study regarding the role of parents in early childhood character education, children's character education is very important for developing children's character, at this time children will imitate their parents' behavior because parents are the first people who children can follow and can influence the formation of children's personalities. The role of parents in children's character education shows that parents set a good example for children, are disciplined and responsible, supervise and direct children to be selective in their relationships